INFRASTRUCTURE SPIN-OFF DECISION IN THE TELECOMMUNICATION COMPANY: PROJECT VALUATION AND AHP ANALYSIS - Ahmad Dirgantoro, Jalu
The negative headwind experienced by the telecommunication industry after the emergence of the telecommunication business on an OTT (over the top) basis suppressed the growth of telecommunications company revenue with lower service prices, limited types of network-based services, and the increasing need for network capex (capital expenditure) to meet customer expectation, giving telco industry experiencing scissor effect with the significant growth of capex and stagnant revenue growth. Several initiatives have been carried out by telco operators in Indonesia to enter the digital economy market, but they have not succeeded in increasing the company's revenue as expected. A new move was made by several operators in Europe to get around this condition by spin off the service telecommunication company (ServeCo) and the telecommunications network provider company (InfraCo, NetCo, and FiberCo), which is a strategy in the context of the consolidation of the telecommunications industry. The largest telecommunications company in Indonesia is currently conducting a diversification strategy review to encourage company growth by leveraging its strategic position as a market leader in the FTTH (Fiber to the Home) business by separating the ServeCo and FiberCo businesses. In this study, the authors try to calculate the business potential and valuation of each potential scenario implemented by ServCo using DCF. To sharpen recommendations to management, the author also conducts a decision analysis using the AHP method to determine the most appropriate scenario to be implemented at ServCo based on several criteria and targets that have been set by ServCo. After calculating the business projections and valuation of each scenario, the authors conducted interviews with experts to weight each of the criteria required and targeted by ServCo for analysis using AHP.